Effect of a micro-copolymer addition on the thermal conductivity of fly ash mortars. (July 2016) - Durán-Herrera, A.; Campos-Dimas, J.K.; Valdez-Tamez, P.L.; Bentz, Dale P.
In this study, a copolymer composed of hollow spherical particles with an average particle size of 90 µm was evaluated as a lightweight aggregate in Portland cement–fly ash mortars to improve the thermal conductivity ( k ) of the composite. Mortars were produced for three different water/binder ratios by mass ( w / b ), 0.4, 0.5, and 0.6. Optimized proportions were obtained for a minimum target compressive strength of 35 kgf/cm 2 (3.4 MPa) according to the requirements of Mexican standards for nonstructural masonry units. Thermal conductivity was determined for dry and saturated samples through the transient plane technique with average results of 0.16 and 0.31 W/(m K), respectively. These values represent an increment of 23% and a reduction of 33% in comparison to an efficient Portland cement–based commercially available thermal insulator.